EFFECT OF CATALYSTS ON WATER AND MOISTURE RELATED PROPERTIES OF BEECH VENEER MODIFIED WITH N-METHYLOL MELAMINE COMPOUNDS - Hien Mai, Trinh (Journal of Forestry Science and Technology, 2016)
The treatments with N-methylol compounds often need to be aided by a catalyst to enhance the condensation reaction with wood polymers and reduce time and temperature of curing process. In this study, two fatty acid modified N-methylol melamine compounds combined with magnesium and aluminium salt catalysts were investigated on water/moisture related properties of the treated beech (Fagus sylvatica.L) veneers. The result showed that: After water soxhlet extraction, mNMM treated veneers displayed higher water repellence effectiveness (WRE) and anti-shrinkage efficiency (ASE) in radial direction with the presence of the catalyst MgCl2 or RB of at least 1.5% concentration (equal to 5% based on stock solution in 30% stock concentration solution of mNMM compounds). This can be explained by: the catalysts could result in better hydrophobic effect for the treatments with mNMM compounds through locking of hydroxyl groups or incorporation of the chemicals in the wood cell wall and the cell lumen. The combination of mNMM compounds (mNMM-1 or mNMM-2) and catalyst MgCl2 induced an increase in equilibrium moisture content (EMCR) and radial swelling (RS) of the treated veneers compared to the control veneers. With increasing concentration of MgCl2 from 1.5 to 4.5%, the EMC and RS were increased because the moisture adsorption of MgCl2 enhanced hygroscopic property of the treated veneers. In contrast, EMCR and RS of modified veneers with a combination of mNMM compounds and catalyst RB were lower than the controls and did not depend on the concentration of catalyst RB.